Renal Transplantation Data from Iraq. (July 2018) - Ali, Ala
Abstract : Renal transplantation in Iraq started in 1973 and has continued until now with live donor transplantation, since deceased donor transplant program is not approved as yet. Long-term transplant data are still scarce. Here we present the data of the Nephrology and Renal Transplantation Center, The Medical City Teaching Hospital, Baghdad and the data of the recently established Basra Center for nephrology and Transplantation in the southern part of Iraq, 2015. Iraq renal transplantation program is a living donor, blood group compatible donor program. Here descriptive statistics used for the baseline data and the Kaplan–Meier method was used to determine the survival rate. All patients received triple immunosuppression (calcineurine inhibitor, mycophenolate mofetil or mycophenolic acid, and steroid). About 500 patients transplanted since January 2009 in the nephrology and renal transplanttaion centre, Baghdad and fifitytransplants till december 2017 in Basra Center for nephrology and Transplantation. The one-year graft survival for related and unrelated donor transplants was 98.9% and 91.8%, respectively. Graft survival was lower (82.9%) in recipients with acute rejection episodes. The patient survival at one-year was 94%. The three year graft and patient survival was 91% and 90%, respectively, and five-year survival for grafts and patients was 87.1% and 88%, respectively. Despite a lot of hurdles, the outcome of the renal transplantation in Iraq is improving. Long-term patient follow-up needs more meticulous attention.